Meet South Africa - Gunther, John, 1901-1970.; Grisha (New York, Harper, 1958)
A portrait of South Africa, published in 1958, which introduces the provinces, history, peoples, and natural resources of a vast area in a period of transition. A portion of this material first appeared in Inside Africa.
Keywords: South Africa -- Description and travel; South Africa -- Description and travel